Self-learning toolkit for intelligent agents and strategic decision-making under conditions of information uncertainty - Donenko , V. (Ways to Improve Construction Efficiency, 2025)
Modern complex systems operate in environments characterized by continuous change, increasing volumes of data, and, at the same time, limited access to complete and reliable information. This creates fundamentally new requirements for strategic decision-making processes, which must account for uncertainty, risks, and the dynamic nature of interactions among participants. Under such conditions, intelligent agents capable of autonomous functioning and self-learning become particularly significant, as they can adapt their behavior in response to changes in the external environment. Self-learning is considered a key mechanism for ensuring the effectiveness of agent activities, based on the accumulation of experience, analysis of previous decisions, and adjustment of interaction strategies. The ability of agents to operate with incomplete, inconsistent, or probabilistic information determines their competitiveness within complex multi-agent systems. An important aspect is the integration of learning and decision-making processes, which enables the formation of coordinated behavioral strategies and ensures effective coordination of actions. The development of a self-learning toolkit involves the application of a set of interconnected approaches, including machine learning methods, elements of game theory, and probabilistic analysis. Such integration creates the basis for adaptive selection of interaction strategies, evaluation of alternative decisions, and prediction of outcomes in environments with a high level of uncertainty. Particular attention is paid to ensuring the agents’ ability to generalize acquired experience, respond rapidly to changes, and minimize the negative impact of information constraints. This contributes to improving the quality of decision-making and ensuring the long-term stability of system functioning. The proposed approach is aimed at overcoming the fragmentation of existing solutions and forming a coherent system in which self-learning and strategic choice are considered as interrelated elements. Its practical significance lies in the possibility of applying such a toolkit in the management of complex organizational structures, digital platforms, and economic systems, where performance largely depends on the ability to operate effectively under conditions of uncertainty.